Contributions of multiple climate hazards and overgrazing to the 2009/2010 winter disaster in Mongolia - Nandintsetseg, Banzragch; Shinoda, Masato; Erdenetsetseg, Baasandai (Natural hazards (Dordrecht), 2018)
Mongolian pastoral husbandry is subject to various climate hazards such as dzud (Mongolian for “severe winter conditions”). Dzud in the 2009/2010 winter affected 80.9% of the country and killed more than 10 million livestock (23.4% of the total). To understand the natural and man-made mechanisms of this dzud , we examined the contributions of dzud -causing factors such as climate hazards (cold temperatures and heavy snow) and winter–spring livestock grazing (measured as overgrazing rate), which created a distinct regional pattern of high livestock mortality using a regression tree method. The regression tree model accounted for 58% of the total spatial variation of the mortality and identified various types of dzud in each region. Results showed that during the 2009/2010 winter, almost all of Mongolia experienced extreme cold temperatures, with abnormally large amounts of snow. In addition, more than half of the territory was overgrazed because of the lower pasture biomass resulting from summer drought and livestock overpopulation. At the regional scale, high livestock mortalities occurred in moderately to heavily overgrazed regions in south-central and western Mongolia, resulting from the combination of these factors. Conversely, areas with lower livestock mortalities (or non- dzud ) coincided with sufficient pasture capacity in the north and east, even under extreme cold and snow. This indicates the importance of controlling the number of livestock to below the pasture carrying capacity regardless of an inter-annually varying climate. Moreover, we identified critical thresholds of each factor across which serious disasters occurred. These thresholds are practically useful for future livestock management of pasture land.